Overwintering strategy of Ips typographus L. (Coleoptera, Curculionidae, Scolytinae) in Croatian spruce forests on lowest elevation : Strategija prezimljavanja smrekovog pisara Ips typographus L. (Coleoptera, Curculionidae, Scolytinae) u hrvatskim smrekovim šumama na najnižoj nadmorskoj visini - Kasumović, Luka (Array, 2019)
Better understanding of overwintering strategy in Ips typographus is crucial in planning of sanitation felling as hot spots recovery measure. Bark and needle litter are present as overwintering niches within the species. At the lowest elevation (500 m a. s. l.) in spruce stands 85 % of beetles overwinter under the bark. Overwintering behavior is elevation adaptable, and portion of beetles which overwinters under the bark of attacked trees increase with decreasing of elevation. The results suggest presence of high plasticity within the species which is well adaptable to changeable habitat and temperature conditions. High in the mountains sanitation felling need to be implemented early in autumn before beetles end the development, while at lower elevations a good result can be achieved with felling early in spring before the start of new generation. During the winter bark peels off the dense attacked tress very often and changes the beetle ratio between niches. This fact needs to be considered in planning of sanitation felling early in spring before fly period of I. typographus.